Hadith #1484 - Sahih al-Bukhari - Safwan bin Y'ala bin Umayya صفوان بن يعلى بن أمية (Sahih al-Bukhari)
Ya’la said to ‘Umar, “Show me the Prophet (ﷺ) when he is being inspired Divinely.” While the Prophet (ﷺ) was at Ji’rana (in the company of some of his Companions) a person came and asked, “O Allah’s Messenger! What is your verdict regarding that person who assumes Ihram for ‘Umra and is scented with perfume ?” The Prophet (ﷺ) kept quiet for a while and he was Divinely inspired (then). ‘Umar beckoned Ya’la. So he came, and the Allah’s Messenger (ﷺ) was shaded with
Grade: Sahih